2010
DOI: 10.1002/bit.22832
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of recombinant human growth hormone at elevated pressures: Pressure effects on PEG‐induced volume exclusion interactions

Abstract: Crystallization of recombinant human growth hormone (rhGH) at elevated pressures was investigated in the presence of 6,000 molecular weight poly(ethylene glycol; PEG-6000). Crystallization of rhGH at atmospheric pressure occurred at a protein concentration of 15 mg/mL in 6% PEG-6000. Crystallization did not occur in the same solutions at 250 MPa. In contrast, at a pressure of 250 MPa in the presence of 8% PEG-6000, rhGH readily crystallized from solutions containing 35 mg/mL rhGH, whereas amorphous precipitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…In previous experiments on the 6 mL‐scale, it was observed that the process was accelerated by addition of small amounts of PEG 10000 (data not shown). This confirmed observations reported in literature (Crisman and Randolph, ; Jion et al, ; Weber et al, ). Therefore, 2% w/v PEG 10000 was added to the pretreated harvests to accelerate the first crystallization steps.…”
Section: Resultssupporting
confidence: 93%
“…In previous experiments on the 6 mL‐scale, it was observed that the process was accelerated by addition of small amounts of PEG 10000 (data not shown). This confirmed observations reported in literature (Crisman and Randolph, ; Jion et al, ; Weber et al, ). Therefore, 2% w/v PEG 10000 was added to the pretreated harvests to accelerate the first crystallization steps.…”
Section: Resultssupporting
confidence: 93%
“…The minimum in J(p) around 150 MPa remains up to 400 mM NaCl, and the J-value increases with increasing NaCl concentration, i.e., with increased screening of the positively charged lysozyme (Fig. The observed pressure dependence of the second virial coefficient is in good agreement with observations by Crisman and Randolph (2010) who studied the crystallization behavior of a human growth hormone and found an increase of the virial coefficient with increasing pressure from 0.1 to 250 MPa. As shown in Fig.…”
Section: Salt Effects On Intermolecular Interactions Of Proteins At Hsupporting
confidence: 86%
“…The latter parameter was explored in a few studies only, such as on subtilisin, glucose isomerase, thaumatin, SNase, RNase A, and lysozyme (Webb et al 1999;Visuri et al 1990;Waghmare et al 2000;Crisman and Randolph 2010;Kadri et al 2003Kadri et al , 2005Jaenicke 1991, 1993;Schall et al 1994;Saikumar et al 1995;Lorber et al 1996;Takano et al 1997;Suzuki et al 2002aSuzuki et al ,b, 2005Nagatoshi et al 2003;Möller et al 2012Möller et al , 2014bJavid et al 2007a, b). The latter parameter was explored in a few studies only, such as on subtilisin, glucose isomerase, thaumatin, SNase, RNase A, and lysozyme (Webb et al 1999;Visuri et al 1990;Waghmare et al 2000;Crisman and Randolph 2010;Kadri et al 2003Kadri et al , 2005Jaenicke 1991, 1993;Schall et al 1994;Saikumar et al 1995;Lorber et al 1996;Takano et al 1997;Suzuki et al 2002aSuzuki et al ,b, 2005Nagatoshi et al 2003;Möller et al 2012Möller et al , 2014bJavid et al 2007a, b).…”
Section: Salt Effects On Intermolecular Interactions Of Proteins At Hmentioning
confidence: 99%
“…Recombinant human growth hormone was expressed in Escherichia coli and purified as described previously. 8,26 HES (Viastarch) was purchased from Fresenius (Graz, Austria), and sucrose and trehalose were purchased from Mallinckrodt Baker (Phillipsburg, New Jersey). All other chemicals were purchased as reagent grade or higher.…”
Section: Methodsmentioning
confidence: 99%